2006
DOI: 10.1038/ng1786
|View full text |Cite
|
Sign up to set email alerts
|

The centrosomal protein nephrocystin-6 is mutated in Joubert syndrome and activates transcription factor ATF4

Abstract: The molecular basis of nephronophthisis, the most frequent genetic cause of renal failure in children and young adults, and its association with retinal degeneration and cerebellar vermis aplasia in Joubert syndrome are poorly understood. Using positional cloning, we here identify mutations in the gene CEP290 as causing nephronophthisis. It encodes a protein with several domains also present in CENPF, a protein involved in chromosome segregation. CEP290 (also known as NPHP6) interacts with and modulates the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
519
2
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(556 citation statements)
references
References 27 publications
21
519
2
13
Order By: Relevance
“…These include Ableson-helper integration-1 (AHI1), Nephrocystin-1 (NPHP1), Centrosomal protein-290 (CEP290), Transmembrane protein 67 (TMEM67) and Retinitis pigmentosa GTPase regulator-interacting protein-like (RPGRIP1L). Each of the genes encodes a modular scaffolding protein without clear enzymatic domains, but sharing several protein-interaction domains of unknown function, suggesting that they may be part of a signaling complex [28][29][30][31][32][33][34][35][36] The Joubert syndrome connection with cilia Although the function of JSRD proteins remains largely unknown, recent evidence suggests roles in either mediating the assembly/stability of cilia or mediating cargo transport within cilia. When tested directly, at least three of the encoded proteins, NPHP1, CEP290 and RPGRIP1L have demonstrated localization to the basal body or cilium [32,[35][36][37], further suggesting a role at the cilium or basal body.…”
Section: Joubert Syndrome and Related Disordersmentioning
confidence: 99%
“…These include Ableson-helper integration-1 (AHI1), Nephrocystin-1 (NPHP1), Centrosomal protein-290 (CEP290), Transmembrane protein 67 (TMEM67) and Retinitis pigmentosa GTPase regulator-interacting protein-like (RPGRIP1L). Each of the genes encodes a modular scaffolding protein without clear enzymatic domains, but sharing several protein-interaction domains of unknown function, suggesting that they may be part of a signaling complex [28][29][30][31][32][33][34][35][36] The Joubert syndrome connection with cilia Although the function of JSRD proteins remains largely unknown, recent evidence suggests roles in either mediating the assembly/stability of cilia or mediating cargo transport within cilia. When tested directly, at least three of the encoded proteins, NPHP1, CEP290 and RPGRIP1L have demonstrated localization to the basal body or cilium [32,[35][36][37], further suggesting a role at the cilium or basal body.…”
Section: Joubert Syndrome and Related Disordersmentioning
confidence: 99%
“…The gene product localizes to renal cilia and to the photoreceptor connecting cilium/transitional zone (9), and is required for early cilia assembly and ciliogenesis (13,14). Additionally, NPHP5 interacts with several proteins responsible for X-linked retinitis pigmentosa (RPGR) (15), LCA, SLSN or Joubert syndrome (CEP290) (10,16,17) and the BBSome subunits that have been implicated in Bardet Biedl Syndrome (18,19). The close interaction of these ciliary proteins, and the overlapping phenotypes observed when defective, suggests that they may function in the same or common pathways.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is apparent that depletion of the other zebrafish centrosomal proteins analysed thus far can also cause defects in the nervous system. Indeed, it has been demonstrated that depletion of the centrosomal protein CEP290 (nephrocystin-6) from zebrafish embryos results in developmental defects of the CNS such as smaller eyes and defects of the brain, 36 thereby highlighting the importance of centrosomal proteins in CNS development. In addition, depletion of CEP290 causes retinal degeneration and kidney abnormalities, because of its function in cilia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depletion of CEP290 causes retinal degeneration and kidney abnormalities, because of its function in cilia. 36,37 Depletion of other centrosomal proteins, Cep70 and Cep131, also results in embryos with a curved tail, shortened body axis and ectopic otoliths, because of shortened cilia. 38 Although not examined here, given the link between centrosomal proteins and ciliary function, and the localisation of NEDD1 to the base of cilia in mouse embryos, 5 it is feasible that zNEDD1 depletion also causes ciliary defects in zebrafish.…”
Section: Discussionmentioning
confidence: 99%